2022
DOI: 10.1177/10406387221104754
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar echinococcosis in a dog in Missouri, USA

Abstract: A 10-y-old, castrated male Boxer dog that was born and had lived in Missouri without any travel history to other states, except for a few trips to Kansas, was presented with a distended abdomen and declined health. Ultrasonographic examination revealed a large hepatic mass, and the dog was euthanized. A postmortem examination revealed that the left liver lobes were largely replaced by a white-to-tan multilobular mass with a cobblestone surface. The lesion also involved the diaphragm. Histologically, hepatic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Despite those limitations, our study provides information that might be used to mitigate the risk of exposure for people to a new haplotype of the zoonotic tapeworm, E. multilocularis, that is emerging as alveolar echinococcosis in Alberta (Massolo et al, 2019;Houston et al, 2021;Santa et al, 2021). Elsewhere in North America, this haplotype has been detected in dogs (Zajac et al, 2020;Kuroki et al, 2022), foxes (Polish et al, 2022;Robbins et al, 2022), and people (Houston et al, 2021;Polish et al, 2021;Schurer et al, 2021;Polish et al, 2022). We showed that compost and consumption of anthropogenic food are associated with a higher prevalence of infected coyote scats, suggesting that aggregations of food that attract both coyotes and prey increase rates of transmission and infection.…”
Section: Discussionmentioning
confidence: 96%
“…Despite those limitations, our study provides information that might be used to mitigate the risk of exposure for people to a new haplotype of the zoonotic tapeworm, E. multilocularis, that is emerging as alveolar echinococcosis in Alberta (Massolo et al, 2019;Houston et al, 2021;Santa et al, 2021). Elsewhere in North America, this haplotype has been detected in dogs (Zajac et al, 2020;Kuroki et al, 2022), foxes (Polish et al, 2022;Robbins et al, 2022), and people (Houston et al, 2021;Polish et al, 2021;Schurer et al, 2021;Polish et al, 2022). We showed that compost and consumption of anthropogenic food are associated with a higher prevalence of infected coyote scats, suggesting that aggregations of food that attract both coyotes and prey increase rates of transmission and infection.…”
Section: Discussionmentioning
confidence: 96%